The carousel value-added tax fraud in the European Emission Trading System - Maria Berrittella; Filippo Alessandro Cimino (Fondazione Eni Enrico Mattei (FEEM), 2012)
In this article, we analyse the effects of the carousel value-added tax fraud in the European carbon market and the legislative measures that the EU Member States could adopt to deal with this phenomena. We use a computable general equilibrium model, called GTAP-E and the version 6 of the GTAP database to evaluate the economy-wide and terms of trade effects. The policy test has been designed for five European countries: Belgium, France, Germany, Italy, Netherlands and the United Kingdom. According to our findings, the legislative measures aimed to remove the VAT fraud in the European Emission Trading System will have positive effects in terms of GDP and welfare in the selected EU Member States.
Keywords: C68; H26; K34; Q58; 330; Domestic Emission Trading; General Equilibrium Analysis; Legislative Measures; Value-added Tax Fraud; Welfare